2009
DOI: 10.1111/j.1349-7006.2009.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA amplification is predictive of poor prognosis in Tunisian patients with nasopharyngeal carcinoma

Abstract: PI3Ks (phosphatidylinositol 3‐kinases) are lipid kinases that regulate signalling pathways involved in cell proliferation, motility, and adhesion. Somatic mutations and amplification of the PIK3CA gene have been reported in various types of human cancers. However, little is known about the frequency and prognosis role of PIK3CA activation in nasopharyngeal carcinoma (NPC). This study was conducted with the aim to screen for PIK3CA mutations in the two hot spot regions (exons 9 and 20) and to investigate for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…For example, PI3K amplification with consequent upregulation of Akt activity in primary NPC tumors has been shown to correlate with a poor prognosis resulting from higher rates of metastasis, irrespective of classification based on differentiation status. 41 Similarly, enhanced rates of distant NPC metastasis have been shown to correlate with increased activation of mTOR and not the differentiation status of the primary tumors. 42 Thus, we have more precisely defined a signaling pathway alteration that correlates with metastatic NPC behavior and confirmed that histological characteristics of focal invasion do not necessarily predict tumor dissemination to distant organs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PI3K amplification with consequent upregulation of Akt activity in primary NPC tumors has been shown to correlate with a poor prognosis resulting from higher rates of metastasis, irrespective of classification based on differentiation status. 41 Similarly, enhanced rates of distant NPC metastasis have been shown to correlate with increased activation of mTOR and not the differentiation status of the primary tumors. 42 Thus, we have more precisely defined a signaling pathway alteration that correlates with metastatic NPC behavior and confirmed that histological characteristics of focal invasion do not necessarily predict tumor dissemination to distant organs.…”
Section: Discussionmentioning
confidence: 99%
“…49 Both mutations and amplification of PIK3C have been the described and the latter may correlate with poor prognosis. [54][55][56] LMP1 causes endocytosis and nuclear accumulation of EGFR where it acts as a transcription factor to increase proliferation. 57 The transcriptional factor hypoxia-inducible factor 1 alpha (HIF-1alfa) may be overexpressed in NPC and is then associated with distant metastasis and poor survival.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…The phosphoinositide 3-kinases (PI3K) are a group of enzymes involved in diverse cellular functions including cell growth, proliferation, differentiation, motility, survival, and intracellular trafficking [44, 45]. Many of these functions relate to the ability of class I PI3K to phosphorylate and activate a serine/threonine protein kinase B (Akt), in turn regulating cell proliferation and preventing apoptosis [46].…”
Section: Pi3k-akt Signaling Pathwaymentioning
confidence: 99%